Protecting Citizens against Bureaucratic Abuse and Maladministration: Why is Nigeria’s Ombudsman Institution not Working Well? - Ifejika, Solomon I. (The Age of Human Rights Journal, 2023)
In 1975, with Decree No. 31, the Federal Military Government of Nigeria established the Public Complaints Commission as the country’s ombudsman institution. Charging it with the responsibility for protecting the citizen’s rights in the administration, Decree No. 31 was an enabling law to the 1974 report of the Public Service Review Panel instituted by the Military Government in 1974 to appraise and revamp the country’s public service. Following Nigeria’s return to democratic rule in 1999, the Commission’s establishment law became known as the Public Complaints Commission Act, CAP P37 of Laws of the Federation of Nigeria 2004, which sustains its existence and operation in the present Fourth Republic. Notwithstanding, the Commission’s performance has largely remained unsatisfactory for being unable to effectively deliver on its statutory mandate. This conceptual study, therefore, investigates the main factors accounting for the ineffectiveness of the Nigerian ombudsman institution. The study relies on qualitative data generated from secondary sources, which was analyzed using the thematic analysis technique of qualitative data analysis. The work finds that, among other issues, the lack of independence and legal capacity to punish offenders, are the key impediments to the effectiveness of the Commission. The study thus recommends, among other things, the amendment of the Commission’s establishment Act to grant the institution independence from the executive and legislative arms of the Nigerian Federal Government and confer on it punitive powers, as workable measures for repositioning the nation’s ombudsman institution for improved performance.